Effects of sodium chloride and sodium tripolyphosphate on the prooxidant properties of hemoglobin in washed turkey muscle system - Haizhou Wu; Sung Yong Park; Mark P. Richards (Food Chemistry: X, 2022)
This study examined the effects of sodium chloride (NaCl) and sodium tripolyphosphate (STPP) on lipid oxidation induced by oxyhemoglobin (oxyHb) in washed turkey muscle (WTM) model. To explore the reasons for observed effects, the pro-oxidant abilities of Hb derivatives (e.g., metHb, oxyHb, hemin, Fe2+, and Fe3+), pH change, and antioxidation of Hb in the presence of NaCl or STPP were also analyzed. The observed lipid oxidation capacity in WTM followed the order metHb > hemin > oxyHb > Fe2+ > Fe3+. Added Fe2+ accelerated auto-oxidation of oxyHb and oxyHb-mediated lipid oxidation. Hb auto-oxidation to metHb increased as the pH decreased from 6.6 to 5.0. NaCl promoted oxyHb-mediated lipid oxidation due to NaCl causing decreased pH value and increased formation of metHb. STPP inhibited oxyHb-mediated lipid oxidation and weakened the pro-oxidative effect of NaCl. This could be attributed to STPP increasing the pH, inactivating free iron, and inhibiting formation of metHb.